SOSIALISASI PEMBERIAN KYPHOSIS EXERCISE UNTUK MEMPERBAIKI POSTUR TUBUH PADA SISWA MADRASAH AL-AMANAH SELAMA COVID-19 - Ika Rahman; Wina Isnaini; Siti Anisa; Nicko Aurora (Insight Power (Kekuatan Wawasan), 2022)
Good posture is a posture that requires minimum energy spending to keep it normal/aligned, while excess energy utilization and efforts will indicate poor posture. This service activity is in the form of counseling related to changes in posture in children caused by repeated activities during the COVID-19 pandemic. This activity was carried out at the Al-Amanah Madrasah, Bandung City with a population of 15 grade 4 elementary school children. To correct bad postures, exercise therapy will be of great help to restore the changes that occur in the spine one example is kyphosis. Kyphosis is one of the cases associated with the curvature of the corners of the spine. Kyphosis exercises can be stretching exercises, strengthening exercises, and spinal movements can also improve postural control, physical functioning, as well as quality of life in society. The result of this activity is that children can understand how important it is to maintain posture, especially in the spine.Keyword: exercise, body posture